Look Who's Talking: On the Heterogeneous Returns to Foreign Language Use at Work among Natives and Migrants in Europe - Zhiling Wang; Thomas de Graaff; Peter Nijkamp (Global Labor Organization (GLO), 2017)
We examine the heterogeneous impacts of foreign language use at work on earnings of both native-born workers and foreign-born workers, using a longitudinal survey, viz. the European Community Household Panel (ECHP) running from 1994 to 2001. Our findings are the following. First, for native-born workers with a tertiary diploma, using a foreign language at work is found to have an unambiguously positive impact on their earnings (2% on average). Second, for foreign-born workers, returns to foreign language use at work is highly complementary to education. Foreign language users below the upper secondary educational level earn significantly less (8%) than those who use the local language at work. Third, with regard to language types, a linguistically distant foreign language gives native-born workers the highest wage premium, while the use of EU official languages pays off the most for foreign-born workers. Fourth, our results do not show evidence that the lack of local language knowledge of low-educated migrants causes these results, as immigrants for whom themother tongue is similar to the local language show a similar pattern.
Keywords: J24; J31; J61; 330; foreign language at work; earnings; native-born; foreign-born